2017
DOI: 10.1002/slct.201701224
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on DNA Binding Properties of 2,10,16,24‐Tetrakis 4‐(4‐hydroxyphenyl)‐1‐phenylethyl) phenoxy)‐Substituted Co(II) and Mg(II) Phthalocyanine Compounds

Abstract: In this study, DNA binding properties of 2,10,16,24‐tetrakis4‐(4‐hydroxyphenyl)‐1‐phenylethyl)phenoxy)phthalocyaninato Co(II) and Mg(II) compounds were analyzed. CT‐DNA was used to determine DNA binding properties of Co(II) (4) and Mg(II) (5) phthalocyanine compounds. The DNA binding properties of compounds 4 and 5 were investigated using electronic absorption titration, fluorescence spectroscopy, cyclic voltammetry, thermal denaturation study, electrophoresis and viscosity measurements in Tris‐buffer (pH 7.0)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In one of them, Arslantaş et al reported DNA binding properties of magnesium (II) Pcs using UV–Vis and fluorescence titration, thermal denaturation, cyclic voltammetry, and viscosity measurement. Their results revealed that magnesium (II) Pcs were bound to ct‐DNA via intercalative mode 44 . Also, Özalp et al reported the interaction of quaternary ammonium‐substituted magnesium (II) Pcs with DNA using Autodock Vina ande Molegro Virtual Docker programs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of them, Arslantaş et al reported DNA binding properties of magnesium (II) Pcs using UV–Vis and fluorescence titration, thermal denaturation, cyclic voltammetry, and viscosity measurement. Their results revealed that magnesium (II) Pcs were bound to ct‐DNA via intercalative mode 44 . Also, Özalp et al reported the interaction of quaternary ammonium‐substituted magnesium (II) Pcs with DNA using Autodock Vina ande Molegro Virtual Docker programs.…”
Section: Resultsmentioning
confidence: 99%
“…Their results revealed that magnesium (II) Pcs were bound to ct-DNA via intercalative mode. 44 Also, Özalp et al reported the interaction of quaternary ammonium-substituted magnesium (II) Pcs with DNA using Autodock Vina ande Molegro Virtual Docker programs. The binding energy and binding constant of quaternary ammonium-substituted magnesium (II) Pcs were calculated as À11.4 kcal/mol and 23 Â 10 7 M À1 , respectively.…”
Section: Ct-dna Binding Properties Of 2b and 3bmentioning
confidence: 99%
“…To verify CT-DNA interactive activities of PcF, thermal denaturation experiments were conducted by absorption spectroscopy of the DNA at varying concentrations in a Tris-HCl buffer at a constant pH 7.1. The melting temperature measurements were conducted at a constant wavelength [22][23][24][25] by using absorption spectroscopy. The sample of CT-DNA and PcF in the buffer solution at a pH of 7.1 containing sodium chloride were increased temperature from 25 to 95 °C every 5 mins.…”
Section: Thermal Melting Experimentsmentioning
confidence: 99%
“…T he DNA binding activity of previously synthesized and characterized 2(3), 9(10), 16 (17), 23 (24) -Tetrakis 4-(4-(2-phenylprop-2-yl) phenoxy) phthalocyanine compound (PcF) with CT-DNA was studied using UV/Vis, emission spectroscopic titrations, the melting temperature, viscosity measurement, and agarose gel electrophoresis methods in a Tris-HCl buffer solution at a pH of 7.1 at room temperature. The absorption titration spectra studies of PcF showed that absorbance intensities were decreased with increasing of concentrations of CT-DNA and the finding proved that the compound interacts with the DNA.…”
Section: Introductionmentioning
confidence: 99%